The History of Kazakhstan in the Early Timurid Historiography - Tulibayeva, Zh.M.; Tulibayev, Т.E. (Journal of Oriental Studies, 2021)
This article considers works of the early Timurid historiography: the Zafar-name, the Shams al-Husn, and the Muntakhab al-Tavarikh-i Mu‘ini. The Zafar-name played an important role in the formation of the Timurid historiography. The first official work on the history of the formation of the Timurid state was created. The historical work the Shams al-Husn was mainly written based on personal observations of Khoja Taj al-Din Salmani. The author, being the court secretary and being in the retinue of Ulugbek, was a witness and participant in many events described by him. The Muntakhab al-Tavarikh-i Mu’ini contains numerous information about the structure of uluses, about the structure of the Turkic and Mongolian troops. The author in the work provides original information about the use of Mongolian and Turkic terms. The historical works of Nizam al-Din Shami, Khoja Taj al-Din Salmani, and Mu‘in al-Din Natanzi are in Persian and represent important sources on the history of Kazakhstan of the 13th – the beginning of the 15th centuries. The political, economic, and family ties between Chingizids and Timurids predefined the special interest of Timurid historians for the description of Desht-i Kipchak and Ulus of Chingizids. The historical works of Timurid historiographers provide information from written sources that have not survived to this day. This research has been funded by the Committee of Science of the Ministry of Education and Science of the Republic of Kazakhstan (Grant No. AP08856086). Keywords: History of Kazakhstan, Timurid historiography, Nizam al-Din Shami, Khoja Taj al-Din Salmani, Mu‘in al-Din Natanzi.